Bonds without borders : a history of the Eurobond market - O'Malley, Chris (John Wiley & Sons, 2015)
Bonds without Borders tells the extraordinary story of how the market developed into the principal source of international finance for sovereign states, supranational agencies, financial institutions and companies around the world. Written by Chris O'Malley - a veteran practitioner and Eurobond market expert- this important resource describes the developments, the evolving market practices, the challenges and the innovations in the Eurobond market during its first half- century. Also, uniquely, the book recounts the development of security and banking regulations and their impact on the development of the international securities markets. In a corporate world crying out for financing, never has an understanding of the international bond markets and how they work been more important. Bonds without Bordersis therefore essential reading for those interested in economic development and preserving a free global market for capital.